Empowering School Committees: Enhancing Facilities and Infrastructure Management at SMKN 1 Makassar - Parinsi, Welimas Kristina; Musa, Anugrah Dewi Lestasi; Musa, Kartika Septiary Pratiwi (Journal Management & Economics Review (JUMPER), 2025)
This study aims to analyze the role of the school committee in managing facilities and infrastructure at SMKN 1 Makassar, focusing on the procurement, maintenance, and disposal of educational facilities. A qualitative approach with a case study design was used for this research. Data were collected through interviews, observations, and documentation, and analyzed inductively. The findings indicate that the school committee plays an active role in all stages of facility and infrastructure management, from planning to disposal. The committee's responsibilities encompass four main functions: advisor, supporter, controller, and mediator between the school and the community. While the committee has effectively carried out its duties, it still faces challenges such as limited land and funding. Nevertheless, the management of facilities and infrastructure at SMKN 1 Makassar has yielded satisfactory results with routine maintenance and procurement based on needs and priorities. This study concludes that the role of the school committee is essential in ensuring the smooth operation and sustainability of high-quality facilities and infrastructure, which in turn supports the quality of education at the school.